Development of a simple technique for watermelon seed extraction - DHALIN D JAYALEKSHMI K RAKESH K. N; Er. Jippu Jacob (Guide) (Tavanur 1999 Department of Farm Power Machinery and Energy)
Development of a simple technique for watermelon seed extraction
Development of a simple technique for watermelon seed extraction